BMT's Role as a Strategic Partner of Sharia Banks: Reviewing the Effectiveness of Channeling Programs in Creating Islamic Financial Inclusion - Melisa Anggreni; Hesi Eka Puteri (LP2M IAIN Palopo, 2023)
This study aims to examine the role of Baitul Maal wa Tamwil (BMT) in increasing the liquidity of Islamic banks in Indonesia. This research uses qualitative research methods with a case study approach. The data used in this study came from several BMTs that have cooperation with Islamic banks in terms of liquidity. The data collection techniques used in this study were observation and documentation. The data analysis technique used in this study is qualitative data analysis with a descriptive analysis model. The results of this study show that BMT acts as a strategic partner of Islamic banks in terms of liquidity, both through the placement of deposit funds, the purchase of Islamic money market instruments, the distribution of productive financing, and the development of Islamic financial inclusion. BMT also has a fairly high liquidity performance, with ratios that show good numbers and are in accordance with standards set by relevant authorities. BMT is influenced by internal and external factors that affect its liquidity, such as BMT size, capital, profitability, asset quality, market sensitivity, and macroeconomic conditions. BMT has differences and similarities with Islamic banks and other non-Islamic bank financial institutions in terms of liquidity, depending on its characteristics, scale, and scope of business. This research provides theoretical and practical implications for the development of theory and practice of liquidity management of Islamic banks and non-Islamic bank financial institutions in Indonesia, as well as providing suggestions for further research.